Optimization of treatment leachates from young, middle-aged and elderly landfills with bipolar membrane electrodialysis - Ilhan, Fatih; Guvenc, Senem Yazici; Avsar, Yasar; Kurt, Ugur; Gonullu, Mustafa Talha (TAYLOR & FRANCIS LTD, 2017)
In this study, a bipolar membrane electrodialysis (BMED) process, which is thought to be an effective treatment method for leachate, was evaluated for leachates of three different ages ('young', 'middle-aged' and 'elderly'). The leachates were pretreated to eliminate membrane fouling problems prior to the BMED process. Experimental studies were carried out to determine optimal operating conditions for the three differently aged leachates in the BMED process. According to the experiment results, there was a high removal efficiency of conductivity determined at 4 membrane - 25 V for young and elderly leachate and at 1 membrane -25 V for middle-aged leachate. It was found that the operating times required to reach the optimal endpoints (at conductivity of about 2 mS/cm) of BMED process were 90, 180 and 300 min for the middle-aged, young and elderly leachates, respectively. Under the optimum operating conditions for the BMED process, removal efficiencies of conductivity and chemical oxygen demand were determined to be 89.5% and 60% for young, 82.5% and 30% for middle-aged and 91.8% and 26% for elderly leachate, respectively.
Keywords: Bipolar membrane; electrodialysis; leachate; deionization; recovery; WASTE-WATER; 2-STAGE ELECTRODIALYSIS; CONVENTIONAL ELECTRODIALYSIS; REVERSE-OSMOSIS; ORGANIC-ACIDS; DESALINATION; PARAMETERS; PERFORMANCE; EXCHANGE; Environmental Sciences & Ecology